2012
DOI: 10.1530/eje-11-1007
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of macroprolactinaemia

Abstract: Objective: Macroprolactinaemia is a condition in which serum prolactin (PRL) consists mainly of large molecular weight PRL (macroPRL). The aim of this study was to examine the natural history of macroprolactinaemia. Design and participants: Six hundred and fifty-four hospital workers participated in this study, including 27 subjects with macroprolactinaemia and 627 controls. MacroPRL and serum PRL concentrations were evaluated over a 4-year period. The ratio of macroPRL was examined by the polyethylene glycol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
3
14
1
Order By: Relevance
“…This observation is in agreement with the previous findings of other authors [18,19] and indicates that big-big prolactin levels remain stable over time.…”
Section: Discussionsupporting
confidence: 94%
“…This observation is in agreement with the previous findings of other authors [18,19] and indicates that big-big prolactin levels remain stable over time.…”
Section: Discussionsupporting
confidence: 94%
“…Macroprolactinemia is defined as a condition in which macroprolactin—which has a molecular mass of >150 kDa and, unlike monomeric PRL, has no action in the human body—is predominantly present in the serum [a PEG-precipitated PRL level greater than 52.8% (mean+2SD) was defined as macroprolactinemia in this study] [15,19]. The prevalence of macroprolactinemia has been estimated at 10–46% in patients with hyperprolactinemia [2026].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that PEG induced precipitation of macroprolactin in serum sample represents a simple, inexpensive, accessible, rapid and reproducible screening technique for hyperprolactinemic sera [19,26,27]. The method is based on different precipitation of proteins according to their molecular weight and solubility in different concentrations of PEG solution.…”
Section: Diagnosismentioning
confidence: 99%
“…It has been generally accepted that a PEG-precipitation ratio greater than 60% (recovery less than 40%) is the cut-off value for the diagnosis of macroprolactinemia. This is because there is no a clear-cut value of "substantial increase", but conventionally a diagnosis of macroprolactinemia is made when more than 30-60% of PRL is in 11 the macroprolactin form of GFC [6,9,24,[26][27][28]. Precipitation with PEG is a widely used screening test for macroprolactin and is easily performed in clinical laboratories.…”
Section: Diagnosismentioning
confidence: 99%